Ancient Egypt a very short introduction - Shaw, Ian 1961- (Oxford University Press, 2021)
In this introduction, Ian Shaw describes how our current ideas about Egypt are based not only on the discoveries made by early Egyptologists but also on fascinating new kinds of evidence produced by modern scientific and linguistic analyses. He also explores the changing influences on our responses to these finds
Includes bibliographical references and index
This edition also issued in print: 2021
Keywords: Egypt / History / To 332 B.C.; Egypt / Civilization / To 332 B.C.; Egypt / Antiquities